Analysis of reliability and belief degree for water distribution system based on fuzzy set theory. Issue 7 (9th August 2021) - Wang, Yumin; Zhu, Guangcan
ABSTRACT: The reliability of water distribution system (WDS) involves imprecise or uncertain parameters. For hydraulic reliability, the uncertain parameters include roughness coefficient, nodal water demand, and the reservoir water level, etc. While water quality reliability is primarily related to chlorine concentrations, with uncertainty parameters including both bulk decay coefficients and wall decay coefficients. The uncertain independent parameters lead to the uncertain results of reliability simulation. As such, fuzzy set theory was proposed to analyze the reliability of WDS and associated belief degree (BD) of calculated reliability. The proposed method was applied to two examples to solve the uncertainty in traditional reliability assessment. The system reliability and BD of WDS were obtained by assumed three uncertainty levels. In addition, the sensitivity analysis of uncertain independent parameters was performed to compare the effects of parameters on simulated reliability and associated BD. The proposed method can help municipalities to make scientific pipe network programming to improve the reliability of WDS.